2012
DOI: 10.1371/journal.pone.0030342
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation and Mechanism Studies of Deoxytylophorinine and Its Derivatives as Potential Anticancer Agents

Abstract: Previous studies indicated that (+)-13a-(S)-Deoxytylophorinine (1) showed profound anti-cancer activities both in vitro and in vivo and could penetrate the blood brain barrier to distribute well in brain tissues. CNS toxicity, one of the main factors to hinder the development of phenanthroindolizidines, was not obviously found in 1. Based on its fascinating activities, thirty-four derivatives were designed, synthesized; their cytotoxic activities in vitro were tested to discover more excellent anticancer agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…In these phytochemical constituents, phenanthroindolizidine alkaloids are characteristic secondary metabolites of some Asclepiadaceae and Moraceae genera including Cynanchum L., Vincetoxicum, Tylophora R. Br., Pergularia L. and Ficus L. [10,17]. These alkaloids exhibit interesting biological activities such as significant cytotoxic [18] and antitumor activities as well as anti-inflammatory [17], antimicrobial [8], antiviral [19], antiasthmatic [20], insecticidal and insect antifeedant [7,8,21] activities.…”
Section: Introductionmentioning
confidence: 99%
“…In these phytochemical constituents, phenanthroindolizidine alkaloids are characteristic secondary metabolites of some Asclepiadaceae and Moraceae genera including Cynanchum L., Vincetoxicum, Tylophora R. Br., Pergularia L. and Ficus L. [10,17]. These alkaloids exhibit interesting biological activities such as significant cytotoxic [18] and antitumor activities as well as anti-inflammatory [17], antimicrobial [8], antiviral [19], antiasthmatic [20], insecticidal and insect antifeedant [7,8,21] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Compound PF403 is a metabolite of the bioactive natural product 13a-(S)-deoxytylophorinine [101] with strong inhibitory activity against HH pathwayhyperactivated MB cells (IC 50 values of 0.013 nM values assayed by MTT assay in human MB DAOY cells). Mechanistic study revealed that PF403 directly binds SMO in a similar manner as vismodegib thereby inhibiting the receptor activity.…”
Section: Cat3mentioning
confidence: 99%
“…CAT3 ( Figure 1A) is a novel phenanthroindolizidine substance that selectively inhibits the hedgehog signaling pathway, demonstrating a significant inhibitory effect in GBM and TMZ-resistant GBM in orthotopic glioblastoma mice models following oral administration [8][9][10]. Moreover, central nervous system toxicity, one of the main obstacles in the development of phenanthroindolizidines, has not been associated with CAT3 [11]. PF403 ( Figure 1B), reporting an in vitro anti-glioma activity approximately 1000 times higher than CAT3 [8] in human cell lines, is the active metabolite of CAT3 synthesized by esterases in vivo and can penetrate the blood-brain barrier to demonstrate an anti-glioma effect [12][13][14].…”
Section: Introductionmentioning
confidence: 99%